Five Additions to The Dictionary of the 18th-century Russian Language - Kruglov, Vasily M. (Slověne, 2017)
The article analyzes the semantics and origins of the words olbrim and obdenkovatʹ. In the Russian language of the age of Peter the Great, the noun olbrim (cf. Belorussian olbrim, obrim; Ukrainian olbrym < Polish olbrzym, obrzym < Greek ὄβρῐμος) was used in the meaning of ‘giant’ and the verb obdenkovatʹ (German abdanken; cf. Polish abdankować) in meaning of ‘to resign.’ The second part of the article analyzes the sense of three contexts in which incorrect interpretation caused several inaccuracies in The Dictionary of the 18th-century Russian Language related to variants of the word olbrim, the semantics of the verb gomonitʹ, and the date of the initial appearance of the borrowed word distrakcija.